The measurement of resilience capacities through the integration of macrolevel and microlevel indicators - d’Errico, Marco; Jumbe, Ellestina; Constas, Mark A. (AKADEMIYA2063, 2021)
Resilience measurement can now be viewed as an established body of research with 15 years of empirical evidence. Across this body of work, measurement studies have typically sought to identify key elements that render some households more resilient than others. There is now ample literature that includes robust and solid methods (Cissé and Barrett 2018; d’Errico, Romano, and Pietrelli 2018; Knippenberg, Jensen, and Constas 2019; Smith and Frankenberger 2018), reviews of methodologies (Barrett et al. 2021), solid evidence on the impact of resilience-enhancing interventions (d’Errico et al. 2020), and evidence on the role of macro and covariate shocks (such as conflict) on resilience capacity (Brück, d’Errico, and Pietrelli 2019).